HUBUNGAN DATA DEMOGRAFI TERHADAP PENGETAHUAN TENTANG ANTIBIOTIK - hasan2002 (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
The irrational use of antibiotics is the main cause of increasing bacterial resistance in the community. Demographic data is thought to influence antibiotic use behavior. This study aims to determine the relationship between demographic data and knowledge about antibiotics in the community. This is a quantitative study with a cross-sectional design. A sample of 218 respondents was selected using convenience sampling and snowball sampling techniques. Data were collected through a questionnaire measuring the level of knowledge about antibiotics and demographic data of the respondents. Data analysis was performed using univariate and bivariate analysis with the Spearman Rank test. Demographic factors such as educational level were significantly associated with knowledge levels and behavior (p < 0.05). Knowledge levels significantly influenced antibiotic usage behavior. Demographic characteristics also play a role in shaping rational antibiotic usage behavior in the community.